Scutellarein inhibits hypoxia- and moderately-high glucose-induced proliferation and VEGF expression in human retinal endothelial cells - Gao Rong; Zhu Bang-hao; Tang Shi-bo; Wang Jiang-feng; Ren Jun (Acta Pharmacologica Sinica, 2016)
Aim: This study was designed to examine the effect of scutellarein on high glucose- and hypoxia-stimulated proliferation of human retinal endothelial cells (HREC). Methods: HREC were cultured under normal glucose (NG), moderate, and high glucose (NG supplemented with 10 or 25 mmol/L D-glucose) and/or hypoxic (cobalt chloride treated) conditions. Cell proliferation was evaluated by a cell counting kit. The expression of vascular endothelial growth factor (VEGF) was assessed by Western blot analysis. Results: The proliferation of HREC was significantly elevated in response to moderately-high glucose and hypoxic conditions. The combination of high glucose and hypoxia did not have any additive effects on cell proliferation. Consistent with the proliferation data, the expression of VEGF was also upregulated under both moderately-high glucose and hypoxic conditions. The treatment with scutellarein (1×10−11–1×10−5 mol/L) significantly inhibited high glucose- or hypoxia-induced cell proliferation and VEGF expression. Conclusion: Both hypoxia and moderately-high glucose were potent stimuli for cell proliferation and VEGF expression in HREC without any significant additive effects. Scutellarein is capable of inhibiting the proliferation of HREC, which is possibly related to its ability to suppress the VEGF expression.